Design of Mobile Digital Healthcare Application For Pregnant Women Based on Android - Sri Nawangsari; Robby Kurniawan Harahap; Harun Al Rasyid; Nina Herlina; Erik Ekowati; Anugriaty Indah Asmarany (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2022)
Regulations for reducing mobility during the Covid-19 pandemic have become a problem for pregnant women. Pregnant women are a group with a high risk of being exposed to the virus. In addition, regular visits to health service centers or Puskesmas are also limited. Then the reduction in routine visits causes the health condition of pregnant women to be unable to be monitored. In this paper, the mobile application was designed and used as a digital guide to help monitor the condition of pregnant women during the pandemic. The research methods used are based on the ADDIE Framework with the software development method using the Experiment and Revision Collaboration (ERC). This mobile application is called Salute Bidan. The Salute Bidan feature is like digitizing some of the midwife tasks which consist of matters relating to pregnancy. The thing that distinguishes this application from other applications is self-screening. This self-screening was developed based on the level of pregnancy risk using the development of 30 risk criteria from the Poedji Rochyati scorecard. This research result is a mobile application in addition to the results of a web application with a web view technique. This app has been tested using black-box testing with use case and the results of all test cases passing.